Diazinon Residues in Rice and Associated Health Risks for Human; A Case Study in Rasht, Iran - Fatemeh Ghanbari; Maryam Kiani Sadr; Masoud Kouckakian; Kobra Melhosseini Darani (Journal of Advances in Environmental Health Research, 2021)
Background: Rice is the most important agricultural crop and the main food in Gilan and Mazandaran Provinces in northern Iran where organophosphorus pesticides, especially diazinon, are used. The excessive use of this insecticide in the paddy fields of Rasht County is a serious threat to people’s health.Methods: In this study, 30 rice samples were collected from five zones in the paddy fields of Rasht in summer. The samples were analyzed when rice is sold to assess the health risk caused by diazinon residues in rice. Following the digestion process, the samples were injected into a High-Performance Liquid Chromatography (HPLC) instrument. Analysis of Variance (ANOVA) and one-sample t-test were respectively used for analyzing data and the Health Risk Index (HRI) for assessing the risk of rice consumption. Results: According to the results, the mean residual diazinon concentration in the rice crops of the five studied zones at the time of consumption (three months after harvest) was 0.4±0.43 mg/kg-1. This was higher than the Iranian standard for permissible diazinon concentration in rice. The results of the health risk assessment for rice consumption indicated an HRI value of 0.13 for rice consumption, which did not constitute a serious risk for people who consume rice regularly. Conclusion: Although the results of this study showed that there are no potential health risks for consumers, with increasing the use of chemical pesticides for crops, to achieve food safety, regular monitoring of pesticide residues in crops is recommended.